TINGKAT KEPUASAN MAHASISWA UNIVERSITAS RIAU DALAM MENGGUNAKAN MEDIA SOSIAL INSTAGRAM STORIES - Damri, Zurriat Fastawa; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The rapid development of technology is not only around us, but has worldwide made changes to the living environment that we live in today. Social media is becoming a new trend in the development of world media. Social media is considered to be a forum for works, ideas, responses, opinions, and even media to express the situation that occurs. These Instagram Stories are the latest features released by the Instagram application. Users can immediately share daily activities in the form of photos and short videos directly to followers by adding certain writing and effects but can only be seen in a limited time, 24 hours. The title of this study is the University of Riau Student Satisfaction Level in Using Instagram Social Media Stories. This study also uses a quantitative approach that is research that describes or explains a problem whose results can be generalized, respondents used in this research are Riau University students, amounting to 166 people, here researchers want to measure several variables from the University of Riau Student Satisfaction Level in Using Social Media Instagram Stories namely, Information, Personal Identity, Integration and Social Interaction, Entertainment. The results of the research obtained using simple linear regression data analysis concluded that this study was in accordance with the theory used, namely the Uses and Gratification Theory. Then this study also shows that the University of Riau Student Satisfaction Level in Using Instagram Stories Social Media has an influence of 3.60% From the average results obtained it can be seen that the average value of GO is greater than the average GS in other words, satisfaction obtained by Riau University students in using stories on social media Instagram. Furthermore, the significance value obtained is also smaller than α = 0.05, which means Ha is accepted, namely the difference between the motives and the satisfaction of University of Riau Students Against the Use of Social Media Instagram Stories.